2018
DOI: 10.2486/indhealth.2017-0162
|View full text |Cite
|
Sign up to set email alerts
|

Towards a wearable sensor system for continuous occupational cold stress assessment

Abstract: This study investigated the usefulness of continuous sensor data for improving occupational cold stress assessment. Eleven volunteer male subjects completed a 90–120-min protocol in cold environments, consisting of rest, moderate and hard work. Biomedical data were measured using a smart jacket with integrated temperature, humidity and activity sensors, in addition to a custom-made sensor belt worn around the chest. Other relevant sensor data were measured using commercially available sensors. The study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…Workers’ health and safety was found to be the most prolific research area. Even though wearable sensors are widely used in clinical settings for the remote monitoring of physiological parameters (e.g., heart rate, blood pressure, body temperature, VO2), only a single study [ 26 ] has employed multiple sensors for the measurement of such metrics in industrial scenarios. This can be attributed to the industries involved being interested in the prevention of work-related incidents that can lead to absence from work, rather than in the normative function of the workers’ body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Workers’ health and safety was found to be the most prolific research area. Even though wearable sensors are widely used in clinical settings for the remote monitoring of physiological parameters (e.g., heart rate, blood pressure, body temperature, VO2), only a single study [ 26 ] has employed multiple sensors for the measurement of such metrics in industrial scenarios. This can be attributed to the industries involved being interested in the prevention of work-related incidents that can lead to absence from work, rather than in the normative function of the workers’ body.…”
Section: Discussionmentioning
confidence: 99%
“…When MoCap systems were combined with EMG sensors ( Table 8 ), the musculoskeletal and postural evaluation of workers during generic physical activities ( Table 5 ) was improved [ 29 , 48 , 49 , 50 , 51 , 54 , 57 ]. Inertial sensors also showed good results for the identification of hazardous events such as trips and falls in the construction industry [ 44 , 58 , 60 , 65 , 66 , 69 , 75 ], but the positions and numbers of the used IMUs were reported to impact on the intra-subject activity identification [ 26 ]. For example, fewer IMUs placed on specific anatomical sections (e.g., hip and neck) showed similar task classification performance than a greater number of IMUs distributed on the entire body [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health. In the early stages, skin conductance (Setz et al, 2010) was utilized in mental health studies; then signals such as heart rate and respiration (Choi et al, 2012); motion, voice, location, sound and light level (Mohiuddin et al, 2013); infrared signals (Masumoto et al, 2017); augmented reality (Keshav et al, 2017); and humidity and temperature (Austad et al, 2018) were added. The timeline (Figure 6) shows that physical signals were utilized more in earlier years; ecological signals were subsequently added.…”
Section: Signalsmentioning
confidence: 99%
“…In a field study it was noted that the provided work clothing was not insulated enough, some workers also removed their gloves to perform fine tasks [10]. Austad et al (2018) concluded the need of a decision-support system based on individual data to support cold stress protection [53].…”
Section: Thermal Exposure and Health Risks In A Changing Climatementioning
confidence: 99%